2016
DOI: 10.4236/ojrad.2016.63031
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Synoptic Reporting of Thyroid Nodules: Potential for Reduction in Number of Patients Undergoing Thyroid Nodule Biopsies

Abstract: Purpose: The objective of the study was to design and implement an electronic synoptic report for thyroid sonography that incorporates the thyroid imaging reporting and data system (TIRADS) and assess potential for reducing unnecessary fine needle aspiration biopsies (FNAB) of thyroid nodules. Methods: The electronic synoptic report was developed using a relational database based on elements from TIRADS and a multidisciplinary consensus statement for thyroid reporting. A retrospective analysis of 138 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Prior studies have demonstrated a lack of completeness in thyroid US reporting. 18 28 29 30 Like Gamme et al, we found that nodule size parameters were most likely to be included, but that other nodule characteristics were not consistently included. In addition, our findings are similar to the results of others demonstrating that only 31 to 43% of US reports incorporated nodule contents and that inclusion of borders, echogenicity, and calcifications was even lower.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Prior studies have demonstrated a lack of completeness in thyroid US reporting. 18 28 29 30 Like Gamme et al, we found that nodule size parameters were most likely to be included, but that other nodule characteristics were not consistently included. In addition, our findings are similar to the results of others demonstrating that only 31 to 43% of US reports incorporated nodule contents and that inclusion of borders, echogenicity, and calcifications was even lower.…”
Section: Discussionsupporting
confidence: 61%
“…28 32 33 Many institutions have adopted TI-RADS reporting of thyroid nodules. Although TI-RADS reporting may reduce unnecessary biopsies, 29 inclusion of the TI-RADS score alone to describe a nodule without cataloging nodule characteristics may limit NLP utility. Future work will be critical in determining the efficacy of NLP tools in annotating structured or synoptic thyroid US reports with detailed TI-RADS features and thus the applicability of NLP tools in thyroid US reports for clinical decision-making or research purposes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selected ultrasound features of thyroid nodules are combined into a score to identify nodules that warrant biopsy or sonographic follow-up. The use of TI-RADS to risk stratify incidental nodules may result in fewer unnecessary biopsies [3]. In order to facilitate the use of TI-RADS, an online calculator was developed.…”
Section: Introductionmentioning
confidence: 99%